Endovascular thrombectomy for acute ischaemic stroke improves and maintains function in the very elderly: A multicentre propensity score matched analysis. (March 2023) - Dunphy, Harriette; Garcia-Esperon, Carlos; Beom Hong, Jae; Manoczki, Csilla; Wilson, Duncan; Lim Alvin Chew, Beng; Beharry, James; Bivard, Andrew; Hasnain, Md Golam; Krauss, Martin; Collecutt, Wayne; Miteff, Ferdi; et al.
Introduction: The very elderly (⩾80 years) are under-represented in randomised endovascular thrombectomy (EVT) clinical trials for acute ischaemic stroke. Rates of independent outcome in this group are generally lower than the less-old patients but the comparisons may be biased by an imbalance of non-age related baseline characteristics, treatment related metrics and medical risk factors. Patients and methods: We compared outcomes between very elderly (⩾80) and the less-old (<80 years) using retrospective data from consecutive patients receiving EVT from four comprehensive stroke centres in New Zealand and Australia. We used propensity score matching or multivariable logistic regression to account for confounders. Results: We included 600 patients (300 in each age cohort) after propensity score matching from an initial group of 1270 patients. The median baseline National Institutes of Health Stroke Scale was 16 (11–21), with 455 (75.8%) having symptom free pre-stroke independent function, and 268 (44.7%) receiving intravenous thrombolysis. Good functional outcome (90-day modified Rankin Scale 0–2) was achieved in 282 (46.8%), with very elderly patients having less proportion of good outcome compared to the less-old (118 (39.3%) vs 163 (54.3%), p  < 0.01). There was no difference between the very elderly and the less-old in the proportion of patients who returned to baseline function at 90 days (56 (18.7%) vs 62 (20.7%), p  = 0.54). All-cause 90-day mortality was higher in the very elderly (75 (25%) vs 49 (16.3%), p  < 0.01), without a difference in symptomatic haemorrhage (very elderly 11 (3.7%) vs 6 (2.0%), p  = 0.33). In the multivariable logistic regression models, the very elderly were significantly associated with reduced odds of good 90-day outcome (OR 0.49, 95% CI 0.34–0.69, p  < 0.01) but not with return to baseline function (OR 0.85, 90% CI 0.54–1.29, p  = 0.45) after adjusting for confounders. Conclusion: Endovascular thrombectomy can be successfully and safely performed in the very elderly. Despite an increase in all-cause 90-day mortality, selected very elderly patients are as likely as younger patients with similar baseline characteristics to return to baseline function following EVT.